ADMINISTRATIVE REFORM IN HEALTH SERVICES THROUGH BALI MANDARA HEALTH INSURANCE (JKBM) TOWARDS GOOD GOVERNANCE IN BALI PROVINCE - Ida Ayu Putu Sri Widnyani (Universitas Sebelas Maret, 2015)
Decentralization gave new hopes to the local government for restructuring. Moreover, the reformation era gave more power to the locals to implement good governance by their own. Good governance itself can be achieved by conducting administrative reform in public services. This article describes the administrative reform of the public service in Bali Province, focusing particularly in the health sector. The administrative reformation of public service in Bali Province requires the role of local governments along with public and non-governmental organization participation. As part of the administrative reformation of health service in Bali Province, Governor released public policy about health assurance namely “JaminanKesehatan Bali Mandara (JKBM)”, that ensures citizens health. This article describes the implementation of JKBM program as an effort of Bali Province government towards Good Governance.Key Words: Administrative Reformation, Health services, and Good Governance.